Cards and carriers: migration, identification and surveillance in Kerala, South India - Mythri Prasad Aleyamma (Contemporary South Asia, 2019)
Identity cards and surveillance practices form an important part of migrant experience and politics. Drawing on fieldwork in construction sites and factory premises in Ernakulam district and a market frequented by migrants in Perumbavoor, a small city near Kochi in Kerala, this paper argues that ID-based surveillance of migrant workers occurs through a complex spatial web of state repression, local power structures and fissures within the classes of workers in Kerala. Migrant workers from North and Northeastern India, and unionized Malayali workers in construction sites and factories in Kerala, battle for and against these cards. Migrant workers resist not necessarily class power that inheres in capital, but the state and surveillance practices.